Gender differences in populations with substance use disorders: A review of the literature - Moon, Allante (2017)
'·A convergence of evidence suggests that women with substance use disorders are more likely than men to face multiple barriers affecting access and entry to substance abuse treatment (Tuchman, 2010). There should never be an issue of receiving substance abuse treatment for any gender and exploring these differences can bring awareness to these issues. Several studies report gender differences in men and women who are experiencing substance use disorders. This thesis is based on a literature review of gender differences in experiencing and treating substance additions among populations of minorities, elderly individuals, and HIV positive individuals. Emphasis is placed on how accessibility to substance abuse services and prevention methods are impacted by gender